Late relapse of classical Hodgkin lymphoma: an analysis of the German Hodgkin Study Group HD7 to HD12 trials - Bröckelmann, Paul Jan; Meißner, Julia (Journal of clinical oncology, 2017)
Purpose: Clinical characteristics, therapeutic approaches, and prognosis of late relapse (LR) in patients with classic Hodgkin lymphoma (cHL) are poorly understood. We performed a comprehensive analysis of LR of Hodgkin lymphoma (LR-HL).MethodsTo estimate the incidence of LR-HL, we retrospectively analyzed 6,840 patients with cHL included in the German Hodgkin Study Group trials HD7 to HD12. Patients who experienced a relapse > 5 years into remission were compared with patients in continued remission for > 5 years and with those who experienced a relapse ≤ 5 years after first diagnosis.ResultsWith a median observation time of 10.3 years, 141 incidences of LR-HL were observed. Cumulative incidences at 10, 15, and 20 years rose linearly and were 2.5%, 4.3%, and 6.9%, respectively. The standardized incidence ratio for HL with respect to age- and sex-matched German reference data was 84.5 (95% CI, 71.2 to 99.7). LR-HL was more frequently observed in patients with early-stage favorable than unfavorable or advanced stage at first diagnosis (15-year cumulative incidence, 5.3% v 3.9% and 3.9%, respectively; P = .01). Overall survival from first diagnosis was worse after LR compared with nonrelapse survivors (10-year estimate, 95.8% v 86.1%; hazard ratio, 2.5; 95% CI, 1.7 to 3.5; P < .001). In patients with LR-HL, survival was better compared with 466 patients with earlier relapse (hazard ratio, 0.6; 95% CI, 0.4 to 0.9, P = .01). Forty-four percent and 49% of patients with LR-HL and earlier relapse, respectively, received stem cell transplantations.ConclusionApart from treatment-associated adverse effects, survivors after initially successful therapy for cHL are at an 85-fold risk for recurrence of disease compared with the general German population. After risk-adapted treatment strategies, especially in early-stage favorable HL, regular clinical follow-up is recommended for timely detection of LR-HL. With adequate treatment, prognosis of LR-HL is better compared with early relapses.